Performance under cyclic loading of square HSS braces with intentional eccentricity (BIEs) - González Ureña, Andrés (2021)
Braces with Intentional Eccentricity (BIEs) are a recently proposed type of lateral bracing system that surmounts several of the shortcomings that Conventional Concentric Braces (CCB) present. As their longitudinal axis is deliberately offset with respect to the line of action of the forces acting on them, BIEs are subject to bending moment in addition to axial forces and, as such, they are naturally less stiff than CCBs. Their stiffness can be adjusted directly by varying the eccentricity. They present a trilinear response to loading in tension, with significant post-yielding stiffness, and a smooth flexural behaviour in compression. Moreover, they are presumed to have longer fracture life under cyclic loading because the onset of local buckling is delayed, due to the strains being more evenly distributed along the bracing member’s length owing to the flexural response. The application of BIEs to building design has been investigated by the authors with results from numerical analyses showing that Frames with Intentionally Eccentric Braces (FIEBs) could present an improved seismic performance, in terms of maximum and residual storey drifts, in comparison with Concentrically Braced Frames (CBFs). Also, as the shear strength in each storey can be adjusted to match closely the demand by varying the eccentricity of the bracing members, the overstrength can be better controlled, which results in requiring less overall material when incorporating capacity design concepts for the complete Seismic-Force-Resisting System (SFRS). In this article, the results of the physical testing under cyclic load of four full-scale ASTM A1085 HSS BIE specimens are presented. The introduction of the eccentricity was achieved by means of two parallel side plates linking the HSS to a knife plate; this configuration was selected for its constructability. The knife plate was detailed to yield in flexure to allow for the unrestrained rotation of the brace ends. The results show that the so constructed BIEs display the expected behaviour and purported benefits of the intentional eccentricity and suggest that the magnitude of the eccentricity plays a significant role in determining their fracture life. Additionally, the results showcased that in lieu of fracture at mid-length after the onset of local buckling, fracture of the tested BIEs could occur at the bracing member’s ends under tensile load, which was attributed to excessive localized rotational demand on the HS member.